Formation of bioethical positions in pharmacy students regarding their educational and consultative activity - I. Yu. Nefedov; I. Yu. Nefedova; M. B. Toirova; P. A. Polezhaeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
This article shows that the participation of pharmacy students in research on bioethics contributes to the formation of their bioethical positions for information and consulting work of the pharmacist in accordance with professional standards. This is discussed on the example of a bioethical position about the value of human life from the moment of conception and the ethics of the implementation and use of hormonal abortive contraceptive. We interviewed 81 young people aged 18 to 20 years and found that 40% of respondents do not believe that human life starts from the moment of conception; almost half of respondents did not know that hormonal contraceptives can interrupt the life of an already conceived human; approximately 30% of respondents did not know about the similar effect of emergency contraceptives. Almost 80% of respondents believe that it is necessary to warn clients about the abortive effect of these drugs. More than 50% of respondents would not use these drugs themselves and recommend them to others, while 11% of the respondents changed their opinion about abortion to negative after participating in the survey. This survey revealed the opinion of young people on these issues and convinced future specialists of the need for a bioethical approach to the information and consulting work of the pharmacist among the population.